2021
DOI: 10.1186/s12903-021-01860-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak and dental health care provision in Nigeria: a national survey

Abstract: Background The impact of the COVID-19 pandemic on the world is unprecedented, posing greater threats to vulnerable healthcare systems, especially in developing countries. This study aimed to assess the knowledge of dental healthcare providers in Nigeria about the disease and evaluate their responses to the preventive measures necessitated by COVID-19. Methods This was an online self-administered questionnaire-based study conducted among dentists pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The study also noted that ultrasonic scaling, crown preparation, third molar disimpaction, and root canal therapy were the highest aerosol generating procedures [16]. Also, about 38% of respondents reported the availability of a dedicated screening bay or tent to attend patients on arrival [16]. Moreover, most of respondents in that study had hand hygiene stations with alcohol-based sanitizer and wash hand basins being utilized in similar proportions.…”
Section: Safety Precaution and Infection Control Practices Among Dent...mentioning
confidence: 74%
See 4 more Smart Citations
“…The study also noted that ultrasonic scaling, crown preparation, third molar disimpaction, and root canal therapy were the highest aerosol generating procedures [16]. Also, about 38% of respondents reported the availability of a dedicated screening bay or tent to attend patients on arrival [16]. Moreover, most of respondents in that study had hand hygiene stations with alcohol-based sanitizer and wash hand basins being utilized in similar proportions.…”
Section: Safety Precaution and Infection Control Practices Among Dent...mentioning
confidence: 74%
“…Moreover, most of respondents in that study had hand hygiene stations with alcohol-based sanitizer and wash hand basins being utilized in similar proportions. Furthermore, about 90% of respondents reported that surgical gloves and surgical masks were the most readily available PPE in the clinic followed by face shields and goggles [16]. Only about 46% and 10% of the study participants reported availability of N95 and KN95 masks respectively in the survey study [16].…”
Section: Safety Precaution and Infection Control Practices Among Dent...mentioning
confidence: 97%
See 3 more Smart Citations